School Teachers’ Perceptions of Most Troublesome Pupil Behaviour - Abdelbasit Gadour (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2012)
A questionnaire based on Wheldall & Merrett’s survey, using a non-random sample was carried out among primary schools in Libya. The study intended to investigate the Libyan teacher’s perceptions of the most troublesome pupil behaviour commonly experienced. Of 89 questionnaires distributed to six primary schools, 84 were returned.  The result showed that more than 85% of Libyan teachers spend more time on problems of order and control than need be.  Behaviours such as lack of concentration, followed by out of seat, and talking out of turn were regarded by overall teachers as the most troublesome.  This result was based on the first and second choice of each question.  The average of class size was 23.70% of whom 3.88% were troublesome children, and of these 2.46% were boys.  However, male teachers found that girls were more troublesome than boys in their classes compared with female teachers.